Protective Effect of Lemon (Citrus limon L.) Ethanol Extract Cream as an Antioxidant Against Exposure to Ultraviolet B Rays in the Skin of Male Wistar (Rattus norvegicus) Rats - Dewa Ayu Putu Sri Ista Dewanti; Desak Ketut Ernawati; Agung Wiwiek Indrayani; Ni Wayan Sucindra Dewi; I Made Jawi (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2020)
Background: Indonesia is an archipelagic country and one of the tropical countries that get sun exposure all the time. Sun exposure can have beneficial and detrimental effects in life. Exposure to radiation can cause acute effects in the form of erythema through the inflammatory process. Antioxidants are substances that can protect the body from damage caused by ROS. Natural antioxidants can be found in vegetables and fruits, one of which comes from lemon extract (Citrus limon L.). Lemon extract is known to have various chemical contents with active compounds in the form of flavonoids and phenols which can act as antioxidants. The aim of this research was to determine the protective effect that can be produced by lemons on UVB exposure in the skin of male wistar rats.Methods: This research uses the true experimental post test only control group design method. Samples were divided into three treatment concentrations, namely ethanol extract of lemon 5%, 10%, and 20%.Result: After testing for normality, the significance value was obtained (p <0.05). Based on the results of the normality and homogeneity test, the results of the data distribution are not normal and the homogeneous tests of the hypotheses used are the Kruskal-Wallis non-parametric test. Kruskal-Wallis non-parametric test results showed a significant difference with the significance value (p = 0.001). The best degree of erythema score was found in the cream of 10% ethanol extract of lemon with an average of 0.8 ± 0.84.Conclusion : The ethanol extract of lemon (Citrus limon L.) cream in a certain dosage has a significant effect on reducing the erythema degree score in the back skin of male Wistar rats (Rattus norvegicus) after exposure to UVB rays.